Strategic Vector of Turkey’s Foreign Policy in Central Asia (Journal of Oriental Studies, 2018)
Under the new geopolitical configuration in Central Asia, the region becomes attractive to leadingactors in international relations such as the US, Russia, the EU and also for regional powers including Turkey.In the current situation around Turkey in the context of the aggravation of the situation in Syria, theposes are posed by the fundamental question of the driving forces and motives of Turkey’s foreign policy.In this connection, the moderate, cooperation oriented on the basis of coinciding interests, implementedby Ankara in the Central Asian direction, attracts attention. The article examines the issues of Turkey’sforeign policy and changes its foreign policy priorities towards Central Asia.